2014
DOI: 10.1515/ijdhd-2014-0350
|View full text |Cite
|
Sign up to set email alerts
|

Service leadership education for university students in Hong Kong: qualitative evaluation

Abstract: This study examined the perceptions of students taking a subject entitled "Service Leadership" at The Hong Kong Polytechnic University which was developed using the model proposed by the Hong Kong Institute of Service Leadership and Management (HKI-SLAM). After taking this subject, students were invited to participate in a qualitative study where they used three descriptors and a metaphor to describe their experiences about the subject. Based on the reflections of 50 students, results showed that 96.1% of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Participants were required to report to what extent they agree or disagree with the five statements (e.g., "The conditions of my life are excellent") on a 6-point Likert scale. Positive youth development was assessed by a 10-item trimmed-version of Chinese Positive Youth Development Scale that has been used in previous studies evaluating the effectiveness of the course "Service Leadership" (Shek et al 2017a;Shek et al 2014). Each item measures one positive youth development attribute, including social competence, cognitive competence, emotional competence, behavioral competence, moral competence, self-determination, belief in the future, clear and positive identity, spirituality, and resilience.…”
Section: Well-beingmentioning
confidence: 99%
“…Participants were required to report to what extent they agree or disagree with the five statements (e.g., "The conditions of my life are excellent") on a 6-point Likert scale. Positive youth development was assessed by a 10-item trimmed-version of Chinese Positive Youth Development Scale that has been used in previous studies evaluating the effectiveness of the course "Service Leadership" (Shek et al 2017a;Shek et al 2014). Each item measures one positive youth development attribute, including social competence, cognitive competence, emotional competence, behavioral competence, moral competence, self-determination, belief in the future, clear and positive identity, spirituality, and resilience.…”
Section: Well-beingmentioning
confidence: 99%
“…Amongst the few evaluation studies on youth leadership, benefits of participation in specific leadership program have been reported (Brungardt & Crawford, 1996;Keating, Rosch, & Burgoon, 2014;Posner, 2009;Rosch & Caza, 2012), with the one-group pretest-posttest design commonly used (e.g., Polleys, 2002;Keating et al, 2014). As to the service leadership education in Hong Kong, its effectiveness has been demonstrated via multiple methods, including the one-group pretest-posttest design (Shek, Lin, Leung, Law, & Li, 2014). Two classes of students who took the credit-bearing subject "Service Leadership" experienced significant improvement in cognitive-behavioral competencies, positive identity, and character.…”
Section: Introductionmentioning
confidence: 99%
“…feedback on this subject [16,17]-it helped them change their mindset such as caring of others and collaboration with each other in serving the community. The findings that the subject was well-received by university students also suggests that students welcomed subjects relevant to their own development.…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation includes objective outcome evaluation, subjective outcome evaluation, process evaluation, and qualitative evaluation (such as focus groups and student reflections). Results from the previous studies showed that students had positive changes in service leadership competencies after taking the subject, and they had very positive perceptions of the subject [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 94%